Razvoj sustava za indiciranje stapnog motora - Bazijanac, Ernest (Promet - Traffic&Transportation, 2012)
The paper deals with the respective measurement system and models for measurement results processing as developed for the requirements of identification of the Diesel engine with supercharging. Subject measurement and measurement results processing have been PC-aided.